Reforming Financial Literacy General Education in Colleges and Universities: Measurement of Financial Literacy level and Training Path of College Students in Higher Vocational Colleges in China - Li, Xu; Min, Xue (Pakistan Journal of Humanities and Social Sciences, 2024)
This study aims to evaluate the financial literacy levels of higher vocational college students in China through a questionnaire survey approach. It seeks to determine the overall financial literacy level and delve into the nuances of gender and family background heterogeneity. Drawing on existing methodological ideas for measuring financial literacy levels, this paper uses a questionnaire survey method to calculate the overall financial literacy level of higher vocational college students in my country. It also conducted an in-depth analysis of the characteristics of college students’ financial literacy levels from the perspectives of gender heterogeneity and family background heterogeneity. The results found that the overall financial literacy level of current college students in China is not high, with a quantitative score of only 39.18 points; regardless of basic financial literacy level, advanced financial literacy level, and overall financial literacy level, male college students' scores are generally higher than female college students. This difference is significant at the 1% level; college students in the financial group who have at least one parent with a financial degree or industry background have a higher financial literacy than college students in the non-financial group. The huge difference in the financial literacy of the two groups of college students is in the level of advanced financial literacy. It is more obvious. The research results suggest that colleges and universities should not only add general education to enhance financial literacy in general education courses but also set up financial literacy education courses at different stages based on students’ gender heterogeneity and family background heterogeneity.